The Challenges of Accountability in a National Museum - Brown, Alistair (Elsevier, 2014)
Using documentary evidence of the Auditor-General's commentaries in the annual reports of the National Museum of Papua New Guinea (PNG) for the period 2004–2012, this paper considers the reporting compliance of the National Museum of PNG. Textual analysis takes into account the complexity of the expectations placed on museums to provide an account of their activities and the mandatory reporting requirements placed on the National Museum of PNG by PNG legislation. Recently, there have been no annual reports generated by the museum, suggesting a low level of compliance. Findings by the state auditor show that the museum often submits late financial statements for audit and receives disclaimers of opinion when they are submitted. The study suggests ways that the museum could achieve greater reporting compliance. It appears that greater funding and staffing of the museum would assist in the preparation of reports.